Brief report: random number generation in autism. - Williams MA; Moss SA; Bradshaw JL; Rinehart NJ (Journal of Autism & Developmental Disorders, 2002)
This study explored the ability of individuals with autism to generate a unique series of digits. Fourteen low-functioning individuals with autism, 14 intellectually disabled individuals, and 14 postgraduate university students generated a series of pseudo-random digits. Individuals with autism were more likely to repeat previous digits than were either of the control groups. The normal control group, however, was less likely to attempt cycling through all digits before repeating. Accordingly, low-functioning individuals with autism may exhibit a shortfall in response inhibition. This finding supports the executive dysfunction theory of autism.